Do nurse navigators bring about fewer patient hospitalisations?. Issue 1 (18th March 2019) - Gordon, Louisa G.; Spooner, Amy J.; Booth, Natasha; Downer, Tai-Rae; Hudson, Adrienne; Yates, Patsy; Geary, Alanna; O'Donnell, Christopher; Chan, Raymond
Abstract : Purpose: Nurse navigators (NNs) coordinate patient care, improve care quality and potentially reduce healthcare resource use. The purpose of this paper is to undertake an evaluation of hospitalisation outcomes in a new NN programme in Queensland, Australia. Design/methodology/approach: A matched case-control study was performed. Patients under the care of the NNs were randomly selected ( n =100) and were matched to historical ( n =300) and concurrent ( n =300) comparison groups. The key outcomes of interest were the number and types of hospitalisations, length of hospital stay and number of intensive care unit days. Generalised linear and two-part models were used to determine significant differences in resources across groups. Findings: The control and NN groups were well matched on socio-economic characteristics, however, groups differed by major disease type and number/type of comorbidities. NN patients had high healthcare needs with 53 per cent having two comorbidities. In adjusted analyses, compared with the control groups, NN patients showed higher proportions of preventable hospitalisations over 12 months, similar days in intensive care and a smaller proportion had overnight stays in hospital. However, the NN patients had significantly more hospitalisations (mean: 6.0 for NN cases, 3.4 for historical group and 3.2 for concurrent group); and emergency visits. Research limitations/implications: As many factors will affect hospitalisation rates beyond whether patients receive NN care, further research and longer follow-up is required. Originality/value: A matched case-control study provides a reasonable but insufficient design to compare the NN and non-NN exposed patient outcomes.